African Continental Free Trade Area (AFCTA) and intra export promotion: The role of digitalization - Kwami Ossadzifo Wonyra; Honoré Tenakoua (West African Journal of Monetary and Economic Integration, 2021)
This paper investigates the impact of the digitalization on intra Africa export. We construct panel data model for 53 African countries covering the period 2005 to 2017 and estimates the model with GMM technique. The results show positive and significant effect of digitalization variables on intra Africa export denoting the important role that access to the internet and telephone can help to achieve the objectives of AfCFTA. African countries should make more competitive their telecommunications sector to reduce costs and to enhance the quality of services. Also, these countries are encouraged to foster the use of ICT as well as improve investments in this sector. An effective liberalization of the telecommunications sector at the continental level with specific commitment can be a good solution to attract investment and promote digitalization for African industrialization and structural transformation.
Keywords: F13; F14; F15; 330; AfCFTA; intra Africa export; digitalization